1989
DOI: 10.3354/meps055217
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of planktonic bioluminescence with other oceanographic parameters from a Norwegian fjord

Abstract: In August 1985 and 1986, a senes of bathyphotometric measurements were made In icefree waters of Vestfjord, Norway, to quantify stimulable in situ bioluminescence. In 1986, we tested and identified the causative bioluminescent plankton. In all profiles, peak or maximum bioluminescence intensity was always within a zone of 15 to 30m below sea surface, with marked decreases below 50m. Maximum biolurninescence intensity from all profiles for both years ranged from 3 X 10' to 2 X 10' photons S-' cc-' of turbulentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 4 publications
2
35
0
Order By: Relevance
“…High fluorescence was absent in the high-CV data cluster, suggesting zooplankton. Lapota et al (1989) demonstrated that Gymnodinium sp. even when correlations between fluorescence and biolumines cence are strong, it does not necessarily confirm that the fluorescence has been due to the luminescent organisms as heterotrophic dinoflagellates may often dominate the planktonic community.…”
Section: Planktonic Communitiesmentioning
confidence: 99%
“…High fluorescence was absent in the high-CV data cluster, suggesting zooplankton. Lapota et al (1989) demonstrated that Gymnodinium sp. even when correlations between fluorescence and biolumines cence are strong, it does not necessarily confirm that the fluorescence has been due to the luminescent organisms as heterotrophic dinoflagellates may often dominate the planktonic community.…”
Section: Planktonic Communitiesmentioning
confidence: 99%
“…The volume flow rate number, a dimensionless flow rate, were calculated was determined by weighing the flow discharge (Schlichting, 1979) for each bioluminescence meacollected over a measured time. Darcy friction surement as previously described (Latz and Rohr, factor, a dimensionless pressure, and Reynolds 1999 Sullivan and Swift, 1994) and 0.5-3 x 109 (Lapota et al, 1989;Swift et al, 1995) t°2 ... photons cell-', respectively.…”
mentioning
confidence: 99%
“…On monthly transits between SDB and SCI an "on-board" sensor system sampled seawater continuously from 3m below the sea surface from a 50m research vessel, the R/V Acoustic Explorer, measuring bioluminescence, seawater temperature, and salinity (Lapota and Losee 1984, Lapota et al 1988, 1989. A vertically deployed bathyphotometer capable of measuring bioluminescence, temperature, salinity, beam attenuation, and chlorophyll fluorescence to a depth of 100m was used at 4 month intervals (summer, fall, winter, spring) at various stations in the Bight to examine the seasonal changes in the biological and physical structure of the water column (Lapota et at.…”
Section: Bioluminescence Measurementsmentioning
confidence: 99%
“…A light budget was calculated to estimate the contribution of light produced by the various species of bioluminescent dinoflagellates in SDB. Light output from each was measured with a laboratory photometer system by stirring individual cells for 30 sec (Lapota et al 1989, Lapota et al 1992. Mean light output for each species was calculated and then multiplied by the number of cells found in each of the monthly plankton samples.…”
Section: Bioluminescent Plankton -San Diego Baymentioning
confidence: 99%
See 1 more Smart Citation